Sistem Informasi Administrasi Disposisi Surat Pada Polresta Jambi - Kurnia, Hanifa; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2024)
Polresta Jambi, located at Jl. Bhayangkara No.1, Talang Banjar, Jambi, is a part of the Jambi City Police Resort. Polresta Jambi has the primary responsibility to maintain security, enforce the law, as well as protect and serve the community across the entire area of Jambi City. Apart from these duties, Polresta Jambi is also involved in day-to-day administration, which includes recording incoming and outgoing correspondence, noting dates of receipt and dispatch, document numbers, subjects, and recipients. However, several obstacles such as manual workflow, incidents of data loss, and issues arising when the administrator is absent from the office have resulted in slower processing of correspondence. To address these issues, the author conducted an analysis and designed an administrative letter disposition system to facilitate Polresta Jambi in future administrative letter disposition processes. This includes: enhancing efficiency in managing letter dispositions, reducing the risk of human errors in administrative processes, expediting workflow and letter processing, and improving transparency in the disposition process. This research resulted in a solution for the existing issues at Polresta Jambi, in the form of a prototype design for an administrative letter disposition information system. This designed system features managing master user data, managing master job position data, managing access role master data, managing disposition data, managing archive data, letter tracking, administering administrative disposition reports, and disposition notifications.